Eksplorasi Kemampuan Koneksi Matematis Siswa Sekolah Dasar Dalam Menyelesaikan Masalah - Baso Intang Sappaile; Ahmad Sofi Yullah; Ika Setiawati; Archristhea Amahoru; Nirmala Dewi (Journal on Education, 2024)
This study aims to explore primary school students' mathematical connection skills in solving mathematical problems. Mathematical connection ability is the ability of students to connect and integrate different mathematical concepts effectively. This research used a qualitative approach with descriptive method. The sample consisted of 20 grade V students at SDN 31 Bontomacinna. Data were collected through tests and interviews, and analysed using quantitative and qualitative approaches. The results showed that students' mathematical connection ability varied, with some students having excellent, good, sufficient, deficient, and very deficient abilities. Data analysis showed that students with better mathematical connection ability tended to obtain higher scores in solving mathematics problems. Students' mathematical connection skills also influenced their overall understanding of mathematical concepts and ability to see connections between topics in mathematics, outside mathematics, and everyday life. This research makes an important contribution to the development of more effective mathematics curriculum and learning strategies. By understanding better about students' mathematical connection abilities, educators can design more interesting and enjoyable learning experiences, and improve students' ability to solve mathematical problems. The implementation of Merdeka Curriculum in Indonesia is also expected to support the development of students' mathematical connection skills at the primary school level.